Answer:
[-7, -5, 0, 1]
Step-by-step explanation:
It always just the x values.
If you are looking for the equation, then it would be y = -x+3
This is the same as y = -1x+3 which is in slope intercept form y = mx+b
m = -1 = slope
b = 3 = y intercept
If you want to graph this, then plot the points (0,3) and (1,2). Then draw a straight line through them both. Extend the line in both directions as much as possible.
For this case we have the following product:
![(x-4) (x + 3) ](https://tex.z-dn.net/?f=%28x-4%29%20%28x%20%2B%203%29%0A)
We must use the distributive property correctly to solve the problem.
We have then:
![x ^ 2 + 3x - 4x - 12 ](https://tex.z-dn.net/?f=x%20%5E%202%20%2B%203x%20-%204x%20-%2012%0A)
Then, we must add similar terms.
We have then:
Answer:
The final product is given by:
option 2